Is hydrogen peroxide an effective mouthwash for reducing the viral load of SARS-CoV-2 in dental clinics? - Emma Burgos-Ramos; Itziar R. Urbieta; Diana Rodríguez (Elsevier, 2022)
Background: Previous studies have demonstrated that SARS-CoV-2 is mainly transmitted by inhalation of aerosols and can remain viable in the air for hours. Viruses can spread in dental settings and put professionals and patients at high risk of infection due to proximity and aerosol-generating procedures, and poor air ventilation. Objectives: The aim of this study was to investigate the effects of a 1% hydrogen peroxide (H2O2) mouth rinse on reducing the intraoral SARS-CoV-2 load. Methods: Portable air cleaners with HEPA filters exposed for 3 months were analysed to test for virus presence in a waiting room (where patients wore a face mask but did not undergo mouth rinsing) and three treatment rooms (where patients wore no mask but carried out mouth rinsing). As CO2 is co-exhaled with aerosols containing SARS-CoV-2 by COVID-19 infected people, we also measured CO2 as a proxy of infection risk indoors. Specific primer and probe RT-PCR were applied to detect viral genomes of the SARS-CoV-2 virus in the filters. Specifically, we amplified the nucleocapsid gene (Nuclv) of SARS-CoV-2. Results: CO2 levels ranged from 860 to 907 ppm, thus indicating low ventilation and the risk of COVID-19 transmission. However, we only found viral load in filters from the waiting room and not from the treatment rooms. The results revealed the efficiency of 1-minute mouth rinsing with 1% H2O2 since patients rinsed their mouths immediately after removing their mask in the treatment rooms. Conclusions: Our findings suggest that dental clinics would be safer and more COVID-19 free by implementing mouth rinsing 1 min with 1% H2O2 immediately after the patients arrive at the clinic.